Opportunities For Funding Innovation - Lewandowska, Lucyna (Comparative Economic Research. Central and Eastern Europe, 2014)
This article is based on the view that firms’ competitiveness lies in their ability to innovate. It points out the incentives that make firms more innovative and the outcomes of implemented innovations. The main focus is given to the sources of innovation funding, in particular leasing, venture capital, private equity, business angels and the NewConnect market, and describes the possibilities of using them. The article stresses that firms seeking capital to grow through innovation can use a wide range of financing options as long as their projects are underpinned by solid documentation, have a specified time horizon, and are attractive for investors.